2018
DOI: 10.1111/bcpt.13148
|View full text |Cite
|
Sign up to set email alerts
|

Signalling pathways involved in p47phox‐dependent reactive oxygen species in platelets of endotoxemic rats

Abstract: Thrombocytopenia during sepsis is associated with a less favourable clinical outcome. Overproduction of reactive oxygen species (ROS) by different cell types contributes to sepsis. Platelets generate ROS, but the upstream pathways of NADPH oxidase activation are not completely understood. Here, we designed experiments in washed platelets from lipopolysaccharide (LPS)-treated rats to investigate the p47 phox activation and ROS generation, and its modulation by c-Src family kinase (c-Src), phosphoinositide 3-kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Interestingly, both Akt [ 45 ] and ERK1/2 [ 43 ] were shown to be involved in PKC signalling in platelets. Indeed, PKC is a signalling hub downstream of several platelet receptors that can also induce p47phox phosphorylation, and thus activate Nox-1 [ 46 ]. Therefore, we investigated the effect of dual inhibition of PDI and Nox-1 on the phosphorylation of PKC substrates, p38 MAPK and p47phox, in addition to Akt and ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both Akt [ 45 ] and ERK1/2 [ 43 ] were shown to be involved in PKC signalling in platelets. Indeed, PKC is a signalling hub downstream of several platelet receptors that can also induce p47phox phosphorylation, and thus activate Nox-1 [ 46 ]. Therefore, we investigated the effect of dual inhibition of PDI and Nox-1 on the phosphorylation of PKC substrates, p38 MAPK and p47phox, in addition to Akt and ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Rats are favorable models for in vitro analyses of platelets as their larger body weight and thus blood volume allows various concomitant measurements. Indeed, rat models have unveiled a number of crucial intracellular responses of platelets to sepsis, including activation of the NLRP3 inflammasome (187), upstream regulation of NADPH subunit p47 phox -dependent ROS production (188) and the contribution of protein kinase C for platelet-mediated leukocyte infiltration and organ injury (189). Furthermore, rats are more commonly used when investigating effects of therapeutic intervention strategies on clinical parameters e.g., hemodynamics.…”
Section: Rodent Models To Study the Role Of Platelets In Sepsismentioning
confidence: 99%
“…However, any role of NOXs in platelet signalling remains somewhat contradictory [ 128 , 129 , 130 , 131 ]. Some studies have reported a fundamental role in experimental platelet ROS production, while others have shown that endotoxemia in rats increased TNF-α levels and promoted platelet-NADPH oxidase activity, via cGMP-PKG and PKC-p47phox signalling pathways [ 22 , 124 , 132 ]. NADPH oxidase (NOX2) activity within neutrophils and specifically ROS production has been suggested to stimulate NETosis, as seen in both human and experimental sepsis [ 104 , 133 ].…”
Section: The Role Of Oxidative and Nitrosative Stress In Sepsis-related Haemostasismentioning
confidence: 99%